IMPLEMENTASI PEMBELAJARAN TAJWID DI MADRASAH TSANAWIYAH SOLEH AL-MUBAROK KECAMATAN TUNGKAL ULU KABUPATEN TANJUNG JABUNG BARAT PROVINSI JAMBI - Anggraini, Della; Anwar, Kasful (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of tajwid learning in improving students' ability to read the Qur'an according to the rules, but in the field, various obstacles are still found such as differences in students' initial abilities, limited time, and low learning motivation. The study aims to describe the implementation of tajwid learning, identify the obstacles faced, and explain the teacher's efforts in overcoming these obstacles in class VIII.3 MTs Soleh Al-Mubarok, Tungkal Ulu District, West Tanjung Jabung Regency, Jambi Province. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research subjects include the principal, tajwid teachers, and class VIII.3 students. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of tajwid learning is carried out through the planning stage, implementation with lecture methods, demonstrations, and reading practice, and evaluation. The obstacles faced include differences in student abilities, limited time, lack of independent practice, and low learning motivation. Teachers' efforts to overcome these obstacles are to provide individual guidance, increase reading practice, create a comfortable learning atmosphere, and establish cooperation with parents. This research has implications for the need to strengthen varied learning strategies and support from the school and family environment to increase the effectiveness of tajwid learning.